A Carnival of Sailing Homes and Shipwrecks<subtitle>Ocean and Society in Hallgrímur Helgason’s Historical Fiction</subtitle> - Auður Aðalsteinsdóttir (Edda)
In his historical novels Sixty Kilos of Sunshine (2018) and Sixty Kilos of Knockouts (2021), Hallgrímur Helgason describes the role of the “herring adventure” in Icelanders’ swift move to modernity whilst gradually moving towards independence from centuries of foreign rule. The author uses grotesque humor and the philosophy of the carnival to offer us his own interpretation of this transitive state. This article discusses some of the story’s carnivalesque characteristics, with references to the theories of Mikhail Bakhtin and an emphasis on postcolonial and gendered aspects.